Japan's corporate governance transformation: Convergence or reconfiguration? - Theo Renou; Rene Carraz; Thierry Burger-Helmchen (Administrative Sciences, 2023)
Japanese firms have historically followed a country-specific model of corporate governance. Yet, Japan has had to adapt its corporate model over the last 30 years, along with the transformation of distinctive characteristics of Japanese capitalism in the same period. We review the historical evolution of Japanese corporate governance over the last three decades with a specific emphasis on the changes in the capital structure of major companies and the efforts to correct ineffective board of directors monitoring. By doing this, we investigate to what extent specific Japanese corporate governance features may explain the nation's economic situation over this period. Thereby, we try to clarify the influences that have presided over recent corporate governance reforms in Japan despite the existence of managerial failures and corporate scandals. This paper places itself into the debate over the diversity of capitalism as it portrays the specificities, differences, and converging trends of Japanese corporate governance practices.
Keywords: 350; corporate scandals; evolution; governance; history; Japan